2016
DOI: 10.12968/denu.2016.43.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and periodontal disease

Abstract: The identification of inflammatory periodontal disease and education in local and systemic risk factors and their management forms the foundation of the treatment of this disease. Nutrition is potentially a modifiable risk factor that could drive or abrogate the underlying oxidative stress in periodontitis. As research in this area is still in its infancy, clinical guidance on the delivery of dietary advice for susceptible patients is scarce. This paper will explain the possible mechanisms linking nutrition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 21 publications
0
25
0
1
Order By: Relevance
“…Studies evaluating the possible effects of total amount of fat were only represented by a single study in Japanese adults [40]. It has been proposed that a high fat intake might lead to enhanced oxidative stress because of an overloading of the Krebs cycle, among other reasons [38,39]. Oxidative stress has been associated with periodontal disease exerting its effects by means of direct damage to cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies evaluating the possible effects of total amount of fat were only represented by a single study in Japanese adults [40]. It has been proposed that a high fat intake might lead to enhanced oxidative stress because of an overloading of the Krebs cycle, among other reasons [38,39]. Oxidative stress has been associated with periodontal disease exerting its effects by means of direct damage to cells.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress has been associated with periodontal disease exerting its effects by means of direct damage to cells. It has been related through the activation of redox-sensitive transcription factors, leading to the production of pro-inflammatory molecules (Figure 2) which enhance and propagate the inflammatory response, elevating the local levels of oxidative stress [38,39]. Unexpectedly, results from the study mentioned suggested a positive association between periodontal health and fat intake [40].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The psychological state of an individual affects the choice, consistency, and quantity of food they consume [35,36]. This may include an increase in the consumption of carbohydraterich foods and soft foods, which do not require as much chewing.…”
Section: Changes To Dietmentioning
confidence: 99%